A dual-targeting peptide facilitates targeting anti-inflammation to attenuate atherosclerosis in ApoE−/− mice. Issue 62 (14th July 2022) - Wu, Bo; Zhong, Yuanzhi; Chen, Jinmin; Pan, Xianmei; Fan, Xianglin; Chen, Peier; Fu, Chenxing; Ou, Caiwen; Chen, Minsheng
Abstract : A dual-targeting peptide towards inflamed endothelial cells is reported, which improves the antiatherogenic effect of anti-inflammatory drug puerarin. Abstract : We report a peptidic dual-targeting drug delivery platform (integrins targeting and self-assembly instructed by matrix metalloproteinases) towards inflamed endothelial cells, which improved the anti-inflammatory ability of the loaded drug ( i.e., puerarin) in vitro and thus improved the antiatherogenic effect of the loaded drug ( i.e., puerarin) in vivo .